Find the last six digits of the number below.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For a quicker computation, we can use the Binomial Theorem:
2 9 5 8 = ( 3 0 − 1 ) 5 8 = k = 0 ∑ 5 8 ( k 5 8 ) 3 0 k ( − 1 ) 5 8 − k = k = 0 ∑ 5 8 ( k 5 8 ) ( − 3 0 ) k
Notice that each term after k = 5 is a multiple of 3 0 6 , and thus will not change the last 6 digits of the answer. Therefore we only need to worry about 0 ≤ k ≤ 5 :
k = 0 : ( 0 5 8 ) ( − 3 0 ) 0 = 1 k = 1 : ( 1 5 8 ) ( − 3 0 ) 1 = − 1 7 4 0 k = 2 : ( 2 5 8 ) ( − 3 0 ) 2 = 2 5 8 ∗ 5 7 ∗ 9 0 0 = 1 4 8 7 7 0 0 k = 3 : ( 3 5 8 ) ( − 3 0 ) 3 = 3 ∗ 2 ∗ 1 5 8 ∗ 5 7 ∗ 5 6 ∗ ( − 2 7 0 0 0 ) ≡ − 1 1 2 0 0 0 ( m o d 1 0 0 0 0 0 0 ) k = 4 : ( 4 5 8 ) ( − 3 0 ) 4 = 4 ∗ 3 ∗ 2 ∗ 1 5 8 ∗ 5 7 ∗ 5 6 ∗ 5 5 ∗ 8 1 0 0 0 0 ≡ 7 0 0 0 0 0 ( m o d 1 0 0 0 0 0 0 ) k = 5 : ( 5 5 8 ) ( − 3 0 ) 5 = 5 ∗ 4 ∗ 3 ∗ 2 ∗ 1 5 8 ∗ 5 7 ∗ 5 6 ∗ 5 5 ∗ 5 4 ∗ ( − 2 4 3 0 0 0 0 0 ) ≡ − 8 0 0 0 0 0 ( m o d 1 0 0 0 0 0 0 )
Therefore, 2 9 5 8 ≡ 1 − 1 7 4 0 + 4 8 7 7 0 0 − 1 1 2 0 0 0 + 7 0 0 0 0 0 − 8 0 0 0 0 0 ≡ 2 7 3 9 6 1 ( m o d 1 0 0 0 0 0 0 )